Fabrication of laminated high entropy alloys using differences in laser melting deposition characteristics of FeCoCrNi and FeCoCrNiAl. (December 2021) - Cai, Yangchuan; Li, Xiaopeng; Xia, Hongbo; Cui, Yan; Manladan, Sunusi Marwana; Zhu, Lisong; Shan, Mengdie; Sun, Da; Wang, Tai; Lv, Xin; Han, Jian
Abstract: Here, in order to develop the metallic materials with excellent relationship between strength and toughness for application, the FeCoCrNi + FeCoCrNiAl-laminated high-entropy alloys (HEAs) had been fabricated by laser melting deposition (LMD) additive manufacturing technique. The process parameter databases for FeCoCrNi and FeCoCrNiAl HEAs were built by orthogonal experiments and statistics method, which helped to select the optimised process parameters for the two HEAs. Then, the differences in the forming process, phase structure, and grain morphology of FeCoCrNi and FeCoCrNiAl HEAs were systematically investigated during the fabrication of the FeCoCrNi + FeCoCrNiAl-laminated HEAs. The results show that variations in surface tension, wettability, and other physical properties between the two HEAs led to significant differences in their LMD processes. Al not only influenced the fabrication process of both HEAs, but also promoted the phase transition from FCC (FeCoCrNi) to BCC (FeCoCrNiAl). In addition, Al also acted as a strong limiting factor to inhibit the effect of supercooling on the grain morphology, which transformed from coarse columnar grains to fine equiaxed grains. The columnar grains, with a preferred orientation in the FeCoCrNi-deposited wall, promoted the suppression of the inhibitive effects of the phase structure and strong limiting factor, led to the growth of the columnar grains in the FeCoCrNiAl-deposited wall, and helped achieve long-distance continuous growth of columnar grains across the interface in the subsequently deposited wall. The methodology used in this study could be meaningful for the exploration of process parameters of LMD, and the discoveries of grain characteristic help to understand the microstructure transition in laminated heterogeneous HEAs fabricated by laser additive manufacturing. Graphical abstract: Unlabelled Image Highlights: Process parameter databases for manufacturing FeCoCrNi and FeCoCrNiAl HEAs by LMD were built. The heterogeneous laminated FeCoCrNi + FeCoCrNiAl HEAs were fabricated by LMD technique. Al element promoted the fine equiaxed grains with BCC structure form in FeCoCrNiAl deposited wall. Columnar grains continuously grew in heterogeneous deposited wall overcome many limiting factors.